Definitions of educational leadership – Arab educators’ perspectives - Abdel Latif Sellami (16937031) (2019)
This study aims to provide a general overview of how educational leadership is defined by Arab educators and education specialists in the Arab region, concentrating on the State of Qatar. The study builds on insights from socio-cultural theory and critical discourse analysis, viewing language as a social practice and thus treats leadership as a form of discursive practice. The study draws on grounded theory and adopts a socio-cultural perspective employing semi-structured interviews conducted with school principals, teachers, educators, educational leaders, educational researchers, and members of the community in Qatar. The results concluded from this study disclose discording views of educational leadership and how it is defined, owing to borrowing the concept from Western educational system models, either by using these terms verbatim or as they are lost in translation. This discord reflects a lack of clarity in using the relevant educational leadership concepts and has arguably led to differences in educational practices and educators’ dispositions and perspectives. Finally, the study concludes with valuable recommendations for educational policy and decision-making and some suggestions for future research. Other Information Published in: International Journal of Leadership in Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13603124.2019.1690701